Issues of Implementation of Public-Private Partnership Projects in the Field of Culture and Art - Kaxramonovna, Yusupaliyeva Dilafruz (Research Parks Publishers, 2023)
This article talks about the essence and current importance of the concept of public-private partnership in the field of culture and art. The decision on public-private partnership in the creative sphere, the positive purpose of the adoption of the decrees, and the tasks to be performed are analyzed.